Impact of diabetes specialist nurses on inpatient care: A systematic review. Issue 9 (18th May 2021) - Akiboye, Funke; Sihre, Harpreet K.; Al Mulhem, Munerah; Rayman, Gerry; Nirantharakumar, Krishnarajah; Adderley, Nicola J.
Abstract: Background: People with diabetes have longer hospital stays and poorer clinical outcomes. Diabetes inpatient specialist nurses have been introduced to improve care. Aims: To assess the evidence for the benefit of diabetes specialist nurses in the inpatient setting. Methods: A systematic search of MEDLINE (ovid), Embase (ovid), CINAHL (EBSCO) and Web of Science core collection from January 1998 to September 2019 was performed using key terms for diabetes specialist nurses and hospital setting. Studies measuring patient care using any standardised or validated outcome measures after introduction of a dedicated diabetes specialist nurse or nursing team were eligible for inclusion and findings reported by narrative synthesis. Results: There were 10 studies which met the inclusion criteria. One was a randomised controlled study and the remaining nine studies were before and after studies with three of them using a time series analysis methodology. The majority reported length of stay (LOS) and showed a reduction in median LOS by between 0.5 and 3 days. Reductions in bed occupancy ranged from 39% to 47%. There was a paucity of evidence for outcomes related to patient care with some measures limited to single studies. These included a 52% reduction in total drug errors, improved patient knowledge, higher patient satisfaction and improved glycaemic control post‐discharge. There was no reduction of mortality observed. Conclusions: These studies suggest a reduction in LOS and improved clinical care for patients with diabetes after the introduction of diabetes inpatient specialist nurses. Future research should examine a range of benefits associated with diabetes inpatient specialist nurse delivered services, including reduction of inpatient complications such as infections and cardiovascular events.